2022
DOI: 10.3389/fnagi.2022.956316
|View full text |Cite
|
Sign up to set email alerts
|

Yijinjing Qigong intervention shows strong evidence on clinical effectiveness and electroencephalography signal features for early poststroke depression: A randomized, controlled trial

Abstract: ObjectiveAlthough Traditional Chinese Yijinjing Qigong Exercise (YJJQE) as mind–body intervention is popularly used among adults to ameliorate depressive symptoms in China, no randomized controlled trials (RCTs) are available to evaluate the effects of YJJQE in patients with poststroke depression (PSD). This study aims to explore the clinical efficacy and the neurological and psychiatric mechanism in brain network functional connectivity underlying electroencephalography (EEG).Materials and methodsA total of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…With simple patterns and directions, and moderate-intensity, safety, and efficacy, Yijinjing is easy to practice and is especially favored by the elderly populations. Previous studies showed that Yijinjing had the potential to improve cognitive function in patients with chronic schizophrenia ( 23 ) and post-stroke ( 24 , 25 ), as well as ameliorate symptoms of people with knee osteoarthritis ( 26 ), ankylosing spondylitis ( 27 ). However, no randomized controlled trials (RCTs) are available to evaluate the effects of Yijinjing in patients with metabolic diseases such as pre-diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…With simple patterns and directions, and moderate-intensity, safety, and efficacy, Yijinjing is easy to practice and is especially favored by the elderly populations. Previous studies showed that Yijinjing had the potential to improve cognitive function in patients with chronic schizophrenia ( 23 ) and post-stroke ( 24 , 25 ), as well as ameliorate symptoms of people with knee osteoarthritis ( 26 ), ankylosing spondylitis ( 27 ). However, no randomized controlled trials (RCTs) are available to evaluate the effects of Yijinjing in patients with metabolic diseases such as pre-diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…17 The results of a systematic study showed that physical and mental exercises, including yijinjing, are beneficial for the recovery of neck pain and disability. 18 Two recent studies on the neuroimaging of patients with stroke after a yijinjing intervention reported that it can modulate brain neural network connections, which may be a central mechanism of its analgesia. 18,19 Although tuina and yijinjing have been widely used in clinical treatment of NCNP in China, few high-level randomized clinical trials have been performed because of the limitations of traditional Chinese medicine research methods.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Two recent studies on the neuroimaging of patients with stroke after a yijinjing intervention reported that it can modulate brain neural network connections, which may be a central mechanism of its analgesia. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations